1169 QUALITY IMPROVEMENT PROGRAMME ON NON-MEDICINAL MANAGEMENT OF POSTURAL HYPOTENSION AMONG MDT MEMBERS IN THE MEDICAL WARDS (COE). (16th January 2023) - Gujjar, A; Kumar, A; Zaheed, A; Liaqat, B
Abstract: Introduction: Postural Hypotension is a very common presentation in the elderly population. Appropriate knowledge to record postural hypotension and non-medicinal management for this is very important among MDT members working in the care of the elderly wards. Method: We set out a questionnaire to assess the knowledge among MDT (multidisciplinary) members. An educational programme was initiated to improve the knowledge among MDT members. A complete audit cycle was done and the knowledge was reassessed with the same questionnaire based on the principles of the PDSA (Plan, Do, Studt and Act) cycle. Results: It showed that the correct way of checking for postural blood pressure improved from 52.4% to 92% in recording the blood pressure. Correct identification of postural blood pressure improved from 33.3% to 88%. Self-rating of confidence to identify correctly postural blood pressure improved from 47.6% to 64% among the MDT Members. It was difficult to compare the answers about non-medicinal methods and exercises to help postural hypotension as there was heterogeneity in answers. It was also not possible to compare the impact of individual interventions on the alleviation of postural blood pressure. Conclusion: Good improvement in the recording and non-medicinal management of Postural hypotension was observed in both the wards among the MDT Members. It is very important to have good knowledge and understanding in the management of this common condition as it helps in the identification and better management.